Preparation of multi-layer composite flame-retardant fiber material combining far infrared rays and negative ions

Through modification treatment and multi-layer composite process, far infrared, negative ion and flame retardant functions are integrated into multi-layer composite fiber materials, solving the problem of functional interaction, improving the flame retardant, far infrared and antibacterial properties of the material, ensuring that High quality and stability of fibers.

CN119239094APending Publication Date: 2025-01-03HEYE HEALTH TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411419007.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to effectively integrate far infrared, negative ion and flame retardant functions into a multi-layer composite fiber material, and the problem of interaction in textiles affects the synergistic performance and performance of the materials.

Method used

Flame retardant preparation by tourmaline powder modification, modified GO preparation, polyester slurry preparation, electrospinning liquid preparation, tourmaline fiber preparation, flame retardant composite fiber and multi-layer composite resistance of electrospinned PPSU/PU fiber sponge The preparation process of fiber-burning materials combines coupling agents, polyvinyl alcohol, silanes, DOPO-GO, PAN/APP and other materials to achieve synergistic performance of functions.

Benefits of technology

The flame retardant performance, far-infrared radiation performance and antibacterial properties of fiber materials are improved, the uniform distribution and high quality of fibers are ensured, and the spinning efficiency and the stability of composite materials are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119239094A_ABST
    Figure CN119239094A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of a multi-layer composite flame-retardant fiber material combining far infrared rays and negative ions. The preparation method comprises the following steps: modification of tourmaline powder, preparation of a flame retardant from modified GO, preparation of polyester slurry, preparation of an electrostatic spinning solution, preparation of tourmaline fibers, preparation of flame-retardant composite fibers, preparation of electrostatic spinning PPSU / PU fiber sponge and preparation of a multi-layer composite flame-retardant fiber material. A gel method and an electrostatic spinning method are creatively combined, the prepared material is beneficial to improving comfort, the flame retardant property of the fiber material is improved, and the fiber material has the advantages of being high in antibacterial property, good in flame retardant property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a new material, in particular to the preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions. Background Art

[0002] As people's requirements for quality of life improve, the functional demand for textiles is also increasing. As emerging functions in textiles, far-infrared function and negative ion function have attracted much attention due to their potential benefits to human health. At the same time, flame retardant performance, as an important indicator of textile safety, cannot be ignored. Therefore, the development of a multi-layer composite fiber material integrating far-infrared, negative ion and flame retardant functions has important market value and application prospects.

[0003] Far-infrared fiber materials can emit far-infrared rays, which resonate with human cells, promote blood circulation, accelerate metabolism, and have certain health benefits for the human body; negative ion fiber materials can release negative ions, which can purify the air, regulate human functions, and relieve fatigue; flame-retardant fiber materials can slow down or prevent the spread of flames when in contact with a fire source, thereby reducing the risk of fire.

[0004] The preparation process of multi-layer composite fiber materials is complex, requiring precise control of the ratio, structure and performance of each layer of materials; integrating the three functions of far infrared, negative ion and flame retardant requires solving the interaction problem between different functional additives to ensure that various functions can be synergistically exerted without affecting the basic properties of the fiber. Through continuous technological exploration and optimization, textile materials with higher added value and broad application prospects can be developed based on important innovations and development directions based on existing technologies. Summary of the invention

[0005] In view of the above problems, the present invention provides a multi-layer composite flame-retardant fiber material combining far infrared and negative ions.

[0006] The first technical purpose of the present invention is to provide an electrospinning solution with excellent performance and good spinnability.

[0007] The second technical purpose of the present invention is to provide a method for preparing a flame-retardant composite fiber with excellent flame retardancy.

[0008] The third technical purpose of the present invention is to provide a preparation process of a multi-layer composite flame-retardant fiber material.

[0009] The invention provides a preparation method for a multi-layer composite flame-retardant fiber material combining far infrared and negative ions, comprising the following steps: modification of tourmaline powder, preparation of flame retardant by modified GO, preparation of polyester slurry, preparation of electrospinning solution, preparation of tourmaline fiber, flame-retardant composite fiber, preparation of electrospinning PPSU / PU fiber sponge, and preparation of multi-layer composite flame-retardant fiber material.

[0010] Preferably, step (1) the tourmaline powder is modified Add tourmaline powder into a three-necked flask and then add coupling agent titanate, polyvinyl alcohol and silane into it respectively; add reaction solvent (toluene) into the flask and continue the reaction in an oil bath; use a centrifuge to separate toluene from the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder; Step (2) Modification of GO to prepare flame retardant DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to DMF, and stirred to fully dissolve DOPO for use; graphene oxide is placed in a DMF solution for ultrasonic dispersion, so that the GO (graphene oxide) sheets are separated and evenly dispersed in DMF (N,N-dimethylformamide); then the dispersed GO is added to the above-dissolved DOPO, and stirred to react under a nitrogen atmosphere; the liquid after the reaction is filtered under reduced pressure to obtain a black powder, which is then repeatedly washed with DMF to remove DOPO that does not participate in the reaction, and finally placed in a vacuum oven for drying to obtain a modified flame retardant DOPO-GO; Step (3) Preparation of polyester slurry The ethylene glycol-based carbon black slurry and terephthalic acid (PTA) are mixed, and the modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (antimony trioxide), followed by ultrasonic stirring to prepare a polyester slurry; Step (4) Preparation of electrospinning solution Using DMF as solvent, respectively prepare a PAN (polyacrylonitrile) solution and a PAN / APP mixed solution, add the solvent and the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) into a glass bottle, stir the solution on a magnetic heating stirrer to make the solution uniformly mixed, and then let it stand to eliminate bubbles, thereby preparing an electrospinning solution; Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into blocks by a rotary crusher, and then crushed into micron coarse powder by a Raymond mill, and finally wet-ground into a micron water slurry by a sand mill; silver compounds such as silver lactate, silver nitrate, and silver sulfate are selected to prepare an aqueous solution as a silver-carrying treatment solution for tourmaline; the water slurry is mixed with the tourmaline silver-carrying treatment solution, the pH is adjusted to a certain value, and stirred in a dark environment to allow the mixture to fully react to complete the silver-carrying treatment of the tourmaline, and then mixed with the viscose fiber solution to control the weight ratio of the silver-carrying tourmaline to the viscose fiber to a certain value; and the viscosity is controlled; after conventional filtration and final filtration with silk cloth, the fineness is controlled for wet spinning, and the speed is controlled for coagulation in an acid bath; after post-treatment such as plasticizing, drawing, cutting, drying, and packaging, the tourmaline fiber is prepared; Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO (dimethyl sulfoxide) solution and ultrasonically dispersed for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of MCC (microcrystalline cellulose) composite fibers under traction; the primary filaments are drawn out in a single strand in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a certain temperature and humidity to dry naturally, thereby obtaining a flame-retardant composite fiber; Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU (polyphenylene sulfone resin) to PU (polyurethane) is fixed; first, DMAc (N, N-dimethylacetamide) is added to a reagent bottle, and the bottle is placed on a stirring table for stirring, and then PPSU particles and PU particles are added in sequence and slowly poured into the reagent bottle, and then PPSU / PU spinning solution is added and BIP (blocked isocyanate) is slowly added with a syringe while stirring, and the mouth of the reagent bottle is sealed with a sealing strip for stirring to obtain the final PPSU / PU electrospinning solution; the spinning solution is sucked with a syringe and fixed on the perfusion system of the spinning machine and the front needle of the syringe is connected to a high-voltage power supply, a layer of polypropylene non-woven fabric is tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, the perfusion system, the slide and the high-voltage power supply are turned on in sequence for spinning to prepare an electrospun PPSU / PU fiber sponge; Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is a certain value, the receiving distance, spinning speed, and spinning voltage are determined, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5), and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes and placed in a cotton drying room. Under thermal bonding, the area and mass of the PTFE woven mesh are selected to pressurize the multi-layer composite fiber web. The PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0011] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) the tourmaline powder is modified Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 1-3%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 90-96° C. for 1-4 hours; use a centrifuge to separate toluene and reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0012] The invention has the advantages that the interface compatibility between tourmaline powder and polymer materials can be effectively improved by adding coupling agent titanate, polyvinyl alcohol, silane and other modifiers. These modifiers can form an organic or inorganic coating layer on the surface of tourmaline powder, increase the interaction force between powder and polymer chain, and help improve the performance of composite materials. Modification treatment can reduce the polarity of the powder surface, reduce agglomeration, and make the powder more evenly dispersed in the matrix, which is beneficial to the performance of the composite material. Modification can also give tourmaline powder antibacterial properties. The modified tourmaline powder can be more evenly dispersed in the spinning solution, reducing blockage and breakage during the spinning process, and improving spinning efficiency and fiber quality.

[0013] Preferably, step (2) modifies GO to prepare a flame retardant 1-6g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to 45-50mLDF, and stirred at 60-65°C for 10-15min to fully dissolve DOPO for use; 1-5g graphene oxide is placed in a DMF solution and ultrasonically dispersed for 20-25min to separate the GO sheets and evenly disperse them in DMF; then the dispersed GO is added to the above-dissolved DOPO, and stirred to react for 1-7.5h under a nitrogen atmosphere (a thermometer is used to ensure that the reaction temperature in a nitrogen atmosphere is 55-60°C); the liquid after the reaction is filtered under reduced pressure to obtain a black powder, which is then repeatedly washed with DMF for 1-4 times to remove DOPO that does not participate in the reaction, and finally placed in a vacuum oven at -50--60°C for 10-15h to obtain a modified flame retardant DOPO-GO.

[0014] The present invention has the advantages that DOPO is combined with GO (graphene oxide), retaining the flame retardant properties of DOPO and utilizing the high specific surface area and excellent thermal stability of GO, so that the modified DOPO-GO flame retardant can more effectively play a flame retardant role in the composite material, thereby improving the flame retardant properties of the composite material; Through ultrasonic dispersion technology, the GO sheets were separated and evenly dispersed in DMF solvent, which effectively avoided the agglomeration of GO. This uniform dispersion state is conducive to the full contact and reaction between DOPO molecules and the GO surface, thereby increasing the grafting rate and coverage of DOPO on the GO surface, which is beneficial to enhancing the flame retardant effect.

[0015] Preferably, in step (3), the polyester slurry is prepared 1-5wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) are mixed, and the ratio of PTA to ethylene glycol is fixed at 1-5:1.4-2.5, and the modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb are added. 2 O 3 (300-350ppm / gPTA), followed by ultrasonic stirring for 15-20min to prepare polyester slurry.

[0016] The present invention has the advantage that DOPO-GO combines the flame retardant properties of DOPO with the high specific surface area and thermal stability of GO, and can form a stable carbon layer when the polyester material burns, effectively isolating oxygen and heat, thereby delaying the combustion process and improving the flame retardant performance; During the preparation process, the ethylene glycol-based carbon black slurry, PTA, modified flame retardant DOPO-GO and catalyst Sb are stirred by ultrasonic stirring. 2 O 3The raw materials can be fully mixed and evenly dispersed in the polyester slurry; the uniform dispersion state is conducive to the uniform distribution of each component in the subsequent processing process, avoiding the performance degradation caused by uneven dispersion.

[0017] Preferably, step (4) preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution are prepared respectively using DMF as a solvent, wherein the spinning concentration of PAN is 5-12wt% and the spinning concentration of APP is 18-30wt%. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) are added into a glass bottle, stirred on a magnetic heating stirrer for 10-12h to uniformly mix the solution, and then allowed to stand for 12-20h to eliminate bubbles, thereby preparing an electrospinning solution.

[0018] The advantage of the present invention is that, by controlling the spinning concentration of PAN and APP and reasonably mixing the solvent, modified tourmaline powder and polyester slurry, the electrospinning solution prepared has excellent spinning performance, including good fluidity, stability and spinnability, which is conducive to forming uniform and continuous fibers during the electrospinning process.

[0019] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, in step (5), the preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 8-25 mm blocks by a rotary crusher, and then crushed into 20-40 micron coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5-2.5 microns; silver compounds such as silver lactate, silver nitrate, and silver sulfate are selected to prepare a 0.05-1M aqueous solution as a silver-carrying treatment solution for tourmaline; the water slurry with a particle size of 0.5-2.5 microns is mixed with the tourmaline silver-carrying treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5-10:90-99.5; the pH is adjusted to 9.5- 10.5, stirring for 1-3 hours in a dark environment to allow it to fully react and complete the silver-loading treatment of tourmaline, and then mixing with the viscose fiber liquid, controlling the weight ratio of silver-loading tourmaline to viscose fiber to be 1-20:99-80; and controlling the viscosity for 30-60 seconds, and the solid content in the silver-loading tourmaline slurry is not less than 15-20% by weight; after 1-3 conventional filtrations and the last 1-3 layers of silk cloth filtration, the fineness is controlled to be between 0.01-1 micron; wet spinning is carried out at a speed of 40-100 m / min, and coagulation is carried out in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the preparation of tourmaline fiber is obtained.

[0020] The invention has the advantages that the refined treatment improves the dispersibility and uniformity of tourmaline in the fiber, which is conducive to giving full play to the functionality of tourmaline; a silver compound is selected to prepare an aqueous solution for silver-loading treatment of tourmaline, which gives the tourmaline fiber antibacterial and antibacterial properties; by controlling the weight ratio of silver to tourmaline and the reaction conditions, the uniformity and effectiveness of the silver-loading treatment are ensured, and the performance of the fiber is further improved.

[0021] Preferably, in step (6), the flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 10-15 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a temperature of 15-20° C. and a humidity of 55-60% to dry naturally to obtain a flame-retardant composite fiber.

[0022] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, step (7) preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU is fixed at 1-4:1-3; first, 40-48g DMAc is weighed into a reagent bottle and placed on a stirring table for stirring, then 5.5-9.6g PPSU particles and 2.4-5.5g PU particles are weighed in turn and slowly poured into the reagent bottle, and then 1.8-2.8g BIP is slowly added to the PPSU / PU spinning solution with a syringe while stirring, and the mouth of the reagent bottle is sealed with a sealing strip and stirred for 12-15h to obtain the final PPSU / PU electrospinning solution; 2-5 5-10mL syringes are used to absorb the spinning solution and fixed on the perfusion system of the spinning machine and the front needle of the syringe is connected to the high-voltage power supply, a layer of polypropylene non-woven fabric is tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, the perfusion system, the slide and the high-voltage power supply are turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

[0023] The present invention has the advantage that the complementary advantages of the two polymer materials are achieved by fixing the mass ratio of PPSU (polyphenylene sulfone) and PU (polyurethane); PPSU has excellent high temperature resistance, chemical corrosion resistance and mechanical strength, while PU has good flexibility and elasticity, and this ratio improves the comprehensive performance of the fiber sponge; PPSU / PU fiber sponge is prepared by electrospinning technology, and polypropylene non-woven fabric is used as the receiving substrate, which improves the adhesion and distribution uniformity of the fiber on the substrate, thereby obtaining a high-quality fiber sponge. The final PPSU / PU fiber sponge has excellent flame retardant properties. The improvement of flame retardant properties makes the fiber sponge have a wider application value in fire prevention, heat insulation and other fields.

[0024] Preferably, step (8) preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 0.6-2.6 mm, the receiving distance is 20-25 cm, the spinning speed is 0.5-0.8 mL / h, the spinning voltage is constant at 15-20 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5) and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes in a cotton drying room, and thermally bonded at 135-150° C. for 1-7 minutes; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0025] The invention has the advantage of uniform spinning of micron-sized fibers. This refined spinning process not only improves the quality of the fibers, but also ensures uniform distribution and good bonding of the fibers in the multi-layer composite structure. Various functional fiber materials such as electrospun PPSU / PU flame-retardant fiber sponge, tourmaline fiber, flame-retardant composite fiber, etc. are compounded together through thermal bonding technology to form a flame-retardant fiber material with a multi-layer structure. By selecting PTFE woven mesh of appropriate area and mass as a pressurizing tool, the thermal bonding effect and the stability of the composite material are further improved.

[0026] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantage that the interface compatibility between tourmaline powder and polymer materials can be effectively improved by adding coupling agent titanate, polyvinyl alcohol, silane and other modifiers. These modifiers can form an organic or inorganic coating layer on the surface of tourmaline powder, increase the interaction between powder and polymer chain, and help improve the performance of composite materials; 2. The invention has the advantages that the modification treatment can reduce the polarity of the powder surface, reduce the agglomeration phenomenon, and make the powder more evenly dispersed in the matrix, which is beneficial to the performance of the composite material. The modification can also give the tourmaline powder antibacterial properties. The modified tourmaline powder can be more evenly dispersed in the spinning solution, reducing the blockage and breakage phenomenon in the spinning process, and improving the spinning efficiency and fiber quality. 3. The present invention has the advantage that DOPO is combined with GO (graphene oxide), retaining the flame retardant properties of DOPO and utilizing the high specific surface area and excellent thermal stability of GO, so that the modified DOPO-GO flame retardant can more effectively play a flame retardant role in the composite material, thereby improving the flame retardant properties of the composite material; 4. The present invention has the advantage that the GO sheets are separated and evenly dispersed in the DMF solvent by ultrasonic dispersion technology, which effectively avoids the agglomeration of GO. This uniform dispersion state is conducive to the full contact and reaction between DOPO molecules and the GO surface, thereby improving the grafting rate and coverage of DOPO on the GO surface, which is conducive to enhancing the flame retardant effect; 5. The present invention has the advantage that DOPO-GO combines the flame retardant properties of DOPO with the high specific surface area and thermal stability of GO, and can form a stable carbon layer when the polyester material burns, effectively isolating oxygen and heat, thereby delaying the combustion process and improving the flame retardant performance; 6. The present invention has the advantage that, during the preparation process, the ethylene glycol-based carbon black slurry, PTA, modified flame retardant DOPO-GO and catalyst Sb are stirred by ultrasonic stirring. 2 O 3 The raw materials can be fully mixed and evenly dispersed in the polyester slurry; the uniform dispersion state is conducive to the uniform distribution of each component in the subsequent processing process, avoiding the performance degradation caused by uneven dispersion; 7. The advantages of the present invention are that, by controlling the spinning concentration of PAN and APP, and rationally mixing the solvent, modified tourmaline powder and polyester slurry, the prepared electrospinning solution has excellent spinning properties, including good fluidity, stability and spinnability, which is conducive to forming uniform and continuous fibers during the electrospinning process; 8. The present invention has the advantages that the refined treatment improves the dispersion and uniformity of tourmaline in the fiber, which is conducive to giving full play to the functionality of tourmaline. The silver compound is selected to prepare an aqueous solution to carry out silver treatment on tourmaline, which gives the tourmaline fiber antibacterial and antibacterial properties; by controlling the weight ratio of silver to tourmaline and the reaction conditions, the uniformity and effectiveness of the silver treatment are ensured, and the performance of the fiber is further improved; 9. The present invention has the advantage that by fixing the mass ratio of PPSU (polyphenylene sulfone) and PU (polyurethane), the advantages of the two polymer materials are complementary; PPSU has excellent high temperature resistance, chemical corrosion resistance and mechanical strength, while PU has good flexibility and elasticity. This ratio improves the comprehensive performance of the fiber sponge; 10. The present invention has the advantages of using electrostatic spinning technology to prepare PPSU / PU fiber sponge and using polypropylene non-woven fabric as a receiving substrate, thereby improving the adhesion and distribution uniformity of the fiber on the substrate, thereby obtaining a high-quality fiber sponge. The final PPSU / PU fiber sponge has excellent flame retardant properties. The improvement of the flame retardant properties makes the fiber sponge have a wider application value in the fields of fire prevention and heat insulation; 11. The advantages of the present invention are that micron-sized fibers can be evenly spun. This refined spinning process not only improves the quality of the fibers, but also ensures uniform distribution and good bonding of the fibers in the multi-layer composite structure. 12. The advantage of the present invention is that various functional fiber materials such as electrospun PPSU / PU flame-retardant fiber sponge, tourmaline fiber, flame-retardant composite fiber, etc. are compounded together through thermal bonding technology to form a flame-retardant fiber material with a multi-layer structure. By selecting a PTFE woven mesh of appropriate area and mass as a pressurizing tool, the thermal bonding effect and the stability of the composite material are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The invention discloses a preparation process of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions. DETAILED DESCRIPTION

[0028] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0029] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0030] Example 1 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 1%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 90°C for 1 hour; use a centrifuge to separate toluene and the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0031] Step (2) Modification of GO to prepare flame retardant 1 g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) was added to 45 mL DMF and stirred at 60 ° C for 10 min to fully dissolve DOPO for use; 1 g graphene oxide was placed in a DMF solution and ultrasonically dispersed for 20 min to separate the GO layers and evenly dispersed in DMF; then the dispersed GO was added to the dissolved DOPO and stirred for reaction for 2 h under a nitrogen atmosphere (a thermometer was used to ensure that the reaction temperature in a nitrogen atmosphere was 55 ° C); the liquid after the reaction was filtered under reduced pressure to obtain a black powder, which was then repeatedly washed with DMF once to remove the DOPO that did not participate in the reaction, and finally dried in a vacuum oven at -50 ° C for 10 h to obtain a modified flame retardant DOPO-GO.

[0032] Step (3) Preparation of polyester slurry 2 wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) were mixed, and the ratio of PTA to ethylene glycol was fixed at 1:1.4. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (300ppm / gPTA), followed by ultrasonic stirring for 15min to prepare a polyester slurry.

[0033] Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared using DMF as a solvent, wherein the spinning concentration of PAN was 6 wt % and the spinning concentration of APP was 18 wt %. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 10 h to uniformly mix the solution, and then allowed to stand for 12 h to eliminate bubbles, thereby preparing an electrospinning solution.

[0034] Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 9 mm blocks by a rotary crusher, and then crushed into 22 μm coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5 μm; a silver compound such as silver lactate, silver nitrate, and silver sulfate is selected to prepare a 0.05 M aqueous solution as a silver-carrying treatment solution for tourmaline; the 0.5 μm particle size water slurry is mixed with the tourmaline silver-carrying treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5:90; the pH is adjusted to 9 .5. Stir for 1 hour in a dark place to allow sufficient reaction to complete the silver-loading treatment of tourmaline, and then mix with the viscose fiber liquid to control the weight ratio of silver-loading tourmaline to viscose fiber to be 1:99; and control the viscosity for 30 seconds, and the solid content in the silver-loading tourmaline slurry is not less than 15% by weight; after 2 conventional filtrations and the last layer of silk cloth filtration, the fineness is controlled to be between 0.01 microns; wet spinning is carried out at a speed of 50 m / min, and coagulation is carried out in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the tourmaline fiber is prepared.

[0035] Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 11 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a temperature of 16° C. and a humidity of 55% to dry naturally, thereby obtaining a flame-retardant composite fiber.

[0036] Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 1:1; first, 42g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring, then 5.5g PPSU particles and 2.4g PU particles were weighed in turn and slowly poured into the reagent bottle, and then 1.8g BIP was slowly added to the PPSU / PU spinning solution with a syringe while stirring, and the mouth of the reagent bottle was sealed with a sealing strip and stirred for 12h to obtain the final PPSU / PU electrospinning solution; the spinning solution was absorbed with 2 5mL syringes and fixed on the perfusion system of the spinning machine and the front needle of the syringe was connected to the high-voltage power supply, a layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, perfusion system, slide and high-voltage power supply were turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

[0037] Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 0.6 mm, the receiving distance is 20 cm, the spinning speed is 0.5 mL / h, the spinning voltage is constant at 15 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5) and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes and thermally bonded at 135° C. in a cotton drying room; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0038] Example 2 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agent titanate, polyvinyl alcohol and silane respectively; make the mass fraction of coupling agent in the whole mixture system be 1%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 96°C for 4 hours; separate toluene from the reaction products of the three reaction solutions by centrifuge, dry and grind the products to obtain modified tourmaline powder; Step (2) Modification of GO to prepare flame retardant 6g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) was added to 50mL DMF, and stirred at 60°C for 10min to fully dissolve DOPO for use; 1g graphene oxide was placed in a DMF solution and ultrasonically dispersed for 25min to separate the GO sheets and evenly dispersed in DMF; then the dispersed GO was added to the dissolved DOPO, and stirred for reaction for 7.5h under a nitrogen atmosphere (a thermometer was used to ensure that the reaction temperature in a nitrogen atmosphere was 60°C); the liquid after the reaction was filtered under reduced pressure to obtain a black powder, which was then washed repeatedly with DMF for 3 times to remove the DOPO that did not participate in the reaction, and finally dried in a vacuum oven at -60°C for 10h to obtain a modified flame retardant DOPO-GO; Step (3) Preparation of polyester slurry 5 wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) were mixed, and the ratio of PTA to ethylene glycol was fixed at 1:1.4. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (350ppm / gPTA), followed by ultrasonic stirring for 20min to prepare polyester slurry; Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared respectively using DMF as a solvent, wherein the spinning concentration of PAN was 12 wt % and the spinning concentration of APP was 20 wt %; the solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 12 h to uniformly mix the solution, and then allowed to stand for 12 h to eliminate bubbles, thereby preparing an electrospinning solution; Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 16 mm blocks by a rotary crusher, and then crushed into 20 μm coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5 μm; a silver compound such as silver lactate, silver nitrate, and silver sulfate is selected to prepare a 0.05 M aqueous solution as a silver-loaded treatment solution for tourmaline; the 0.5 μm particle size water slurry is mixed with the tourmaline silver-loaded treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5:99.5; the pH is adjusted to 9.5, stirring for 1 hour in a dark environment to allow it to fully react and complete the silver-loading treatment of tourmaline, and then mixing with viscose fiber liquid, controlling the weight ratio of silver-loading tourmaline to viscose fiber to be 1:80; and controlling the viscosity for 35 seconds, and the solid content in the silver-loading tourmaline slurry is not less than 20% by weight; after 3 conventional filtrations and the last 2 layers of silk cloth filtration, the fineness is controlled to be between 0.01 microns; wet spinning is carried out at a speed of 70 meters per minute, and coagulation is carried out in an acid bath; after plasticizing, drafting, cutting, drying, packaging and other post-processing, the preparation of tourmaline fiber is obtained; Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 10 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath, and a wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment of 20°C and 60% for natural air drying to obtain a flame-retardant composite fiber; Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 4:1; first, 48g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring, then 9.6g PPSU particles and 2.4g PU particles were weighed in sequence and slowly poured into the reagent bottle, then PPSU / PU spinning solution was added and 1.8g BIP was slowly added with a syringe while stirring, and the mouth of the reagent bottle was sealed with a sealing strip and stirred for 12h to obtain the final PPSU / PU electrospinning solution; the spinning solution was absorbed with 5 10mL syringes and fixed on the perfusion system of the spinning machine and the front needle of the syringe was connected to the high-voltage power supply, a layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, perfusion system, slide and high-voltage power supply were turned on in sequence for spinning to prepare an electrospun PPSU / PU fiber sponge; Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 0.6 mm, the receiving distance is 20 cm, the spinning speed is 0.8 mL / h, the spinning voltage is constant at 20 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5) and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes and thermally bonded at 135° C. in a cotton drying room; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0039] Example 3 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 2%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 92°C for 3 hours; use a centrifuge to separate toluene and the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0040] Step (2) Modification of GO to prepare flame retardant 3g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) was added to 46ml DMF and stirred at 62°C for 13min to fully dissolve DOPO for later use; 3g graphene oxide was placed in a DMF solution and ultrasonically dispersed for 23min to separate the GO sheets and evenly dispersed in DMF; then the dispersed GO was added to the dissolved DOPO and stirred for reaction under a nitrogen atmosphere for 5.5h (a thermometer was used to ensure that the reaction temperature in a nitrogen atmosphere was 56°C); the liquid after the reaction was filtered under reduced pressure to obtain a black powder, which was then washed repeatedly with DMF twice to remove the DOPO that did not participate in the reaction, and finally dried in a vacuum oven at -55°C for 13h to obtain a modified flame retardant DOPO-GO.

[0041] Step (3) Preparation of polyester slurry 3 wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) were mixed, and the ratio of PTA to ethylene glycol was fixed at 5:2.5. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (320ppm / gPTA), followed by ultrasonic stirring for 16min to prepare a polyester slurry.

[0042] Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared using DMF as a solvent, wherein the spinning concentration of PAN was 9 wt % and the spinning concentration of APP was 25 wt %. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 11 h to uniformly mix the solution, and then allowed to stand for 15 h to eliminate bubbles, thereby preparing an electrospinning solution.

[0043] Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 15 mm blocks by a rotary crusher, and then crushed into 35 μm coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5 μm; a silver compound such as silver lactate, silver nitrate, and silver sulfate is selected to prepare a 0.05 M aqueous solution as a silver-loaded treatment solution for tourmaline; the 0.5 μm particle size water slurry is mixed with the tourmaline silver-loaded treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5:90; the pH is adjusted to 9.5, stirring for 2 hours in a dark environment to allow it to fully react and complete the silver-loading treatment of tourmaline, and then mixing with the viscose fiber liquid, controlling the weight ratio of silver-loading tourmaline to viscose fiber to be 1:99; and controlling the viscosity to 36 seconds, the solid content of the silver-loading tourmaline slurry is not less than 16% by weight; after 2 conventional filtrations and the last 2 layers of silk cloth filtration, the fineness is controlled to be between 1 micron; wet spinning is carried out at a speed of 100 m / min, and coagulation is carried out in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the preparation of tourmaline fiber is obtained.

[0044] Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 15 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a temperature of 15°C and a humidity of 56% to dry naturally, thereby obtaining a flame-retardant composite fiber.

[0045] Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 4:1; first, 45g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring, then 5.5g PPSU particles and 5.5g PU particles were weighed in turn and slowly poured into the reagent bottle, and then PPSU / PU spinning solution was added and 2.8g BIP was slowly added with a syringe while stirring, and the mouth of the reagent bottle was sealed with a sealing strip and stirred for 13h to obtain the final PPSU / PU electrospinning solution; the spinning solution was absorbed with 3 8mL syringes and fixed on the perfusion system of the spinning machine and the front needle of the syringe was connected to the high-voltage power supply, a layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, perfusion system, slide and high-voltage power supply were turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

[0046] Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 1.6 mm, the receiving distance is 22 cm, the spinning speed is 0.6 mL / h, the spinning voltage is constant at 17 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5) and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes and thermally bonded at 145° C. in a cotton drying room; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0047] Example 4 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 3%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 96°C for 4 hours; use a centrifuge to separate toluene and the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0048] Step (2) Modification of GO to prepare flame retardant 6g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) was added to 50mL DMF and stirred at 65°C for 15min to fully dissolve DOPO for later use; 5g graphene oxide was placed in a DMF solution and ultrasonically dispersed for 25min to separate the GO sheets and evenly dispersed in DMF; then the dispersed GO was added to the dissolved DOPO and stirred for reaction under a nitrogen atmosphere for 7.5h (a thermometer was used to ensure that the reaction temperature in a nitrogen atmosphere was 60°C); the liquid after the reaction was filtered under reduced pressure to obtain a black powder, which was then washed repeatedly with DMF for 4 times to remove the DOPO that did not participate in the reaction, and finally dried in a vacuum oven at -50°C for 15h to obtain a modified flame retardant DOPO-GO.

[0049] Step (3) Preparation of polyester slurry 2 wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) were mixed, and the ratio of PTA to ethylene glycol was fixed at 5:1.4. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (320ppm / gPTA), followed by ultrasonic stirring for 16min to prepare a polyester slurry.

[0050] Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared using DMF as a solvent, wherein the spinning concentration of PAN was 12 wt % and the spinning concentration of APP was 30 wt %. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 12 h to uniformly mix the solution, and then allowed to stand for 20 h to eliminate bubbles, thereby preparing an electrospinning solution.

[0051] Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 25 mm blocks by a rotary crusher, and then crushed into 40 μm coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 2.5 μm; a 1M aqueous solution of silver compounds such as silver lactate, silver nitrate, and silver sulfate is selected as a silver-carrying treatment solution for tourmaline; the 2.5 μm particle size water slurry is mixed with the tourmaline silver-carrying treatment solution, and the weight ratio of silver to tourmaline is controlled to be 10:99.5; the pH is adjusted to 10 .5. Stir for 3 hours in a dark place to allow sufficient reaction to complete the silver-loading treatment of tourmaline, and then mix with viscose fiber liquid, control the weight ratio of silver-loading tourmaline to viscose fiber to be 20:80; and control the viscosity for 60 seconds, the solid content in the silver-loading tourmaline slurry is not less than 20% by weight; after 3 conventional filtrations and the last 3 layers of silk cloth filtration, control the fineness to be between 1 micron; carry out wet spinning, control the speed to 100 m / min, and coagulate in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the tourmaline fiber is prepared.

[0052] Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 15 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment of 20°C and 60% for natural air drying to obtain a flame retardant composite fiber.

[0053] Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 4:3; first, 48g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring, then 9.6g PPSU particles and 5.5g PU particles were weighed in turn and slowly poured into the reagent bottle, and then PPSU / PU spinning solution was added and 2.8g BIP was slowly added with a syringe while stirring, and the mouth of the reagent bottle was sealed with a sealing strip and stirred for 15h to obtain the final PPSU / PU electrospinning solution; the spinning solution was absorbed with 5 10mL syringes and fixed on the perfusion system of the spinning machine and the front needle of the syringe was connected to the high-voltage power supply, a layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, perfusion system, slide and high-voltage power supply were turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

[0054] Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 2.6 mm, the receiving distance is 25 cm, the spinning speed is 0.8 mL / h, the spinning voltage is constant at 20 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5), and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes and thermally bonded in a cotton drying room at 150° C. for 7 minutes; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0055] Comparative Example 1 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 8%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 98°C for 10 hours; use a centrifuge to separate toluene and the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0056] Step (2) Modification of GO to prepare flame retardant 10g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) was added to 60mL DMF, and stirred at 80°C for 20min to fully dissolve DOPO for later use; 8g graphene oxide was placed in a DMF solution and ultrasonically dispersed for 30min to separate the GO sheets and evenly dispersed in DMF; then the dispersed GO was added to the dissolved DOPO, and stirred for reaction under a nitrogen atmosphere for 15h (a thermometer was used to ensure that the reaction temperature in a nitrogen atmosphere was 65°C); the liquid after the reaction was filtered under reduced pressure to obtain a black powder, which was then washed repeatedly with DMF for 5 times to remove the DOPO that did not participate in the reaction, and finally dried in a vacuum oven at -60°C for 20h to obtain a modified flame retardant DOPO-GO.

[0057] Step (3) Preparation of polyester slurry 6 wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) were mixed, and the ratio of PTA to ethylene glycol was fixed at 5:2.5. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb 2 O 3 (350ppm / gPTA), followed by ultrasonic stirring for 35min to prepare a polyester slurry.

[0058] Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared using DMF as a solvent, wherein the spinning concentration of PAN was 25 wt % and the spinning concentration of APP was 35 wt %. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 15 h to uniformly mix the solution, and then allowed to stand for 25 h to eliminate bubbles, thereby preparing an electrospinning solution.

[0059] Step (5) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 20 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment of 25°C and 65% for natural air drying to obtain a flame retardant composite fiber.

[0060] Step (6) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 4:3; first, 50g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring, then 6.5g PPSU particles and 8.5g PU particles were weighed in turn and slowly poured into the reagent bottle, and then PPSU / PU spinning solution was added and 3.5g BIP was slowly added with a syringe while stirring, and the mouth of the reagent bottle was sealed with a sealing strip and stirred for 20h to obtain the final PPSU / PU electrospinning solution; the spinning solution was absorbed with 5 15mL syringes and fixed on the perfusion system of the spinning machine and the front needle of the syringe was connected to the high-voltage power supply, a layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, perfusion system, slide and high-voltage power supply were turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

[0061] Step (7) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 3.6 mm, the receiving distance is 25 cm, the spinning speed is 0.9 mL / h, the spinning voltage is constant at 25 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, and the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (6) is placed in it. The flame-retardant composite fiber prepared in step (5) is sprayed with two larger polytetrafluoroethylene (PTFE) woven meshes and thermally bonded at 250°C for 6 minutes in a cotton drying room; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0062] Comparative Example 2 Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 1%; add reaction solvent (toluene) into the flask and continue to react for 2 hours in an oil bath at 85°C; use a centrifuge to separate toluene and the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

[0063] Step (2) Preparation of polyester slurry 2wt% ethylene glycol-based carbon black slurry was mixed with terephthalic acid (PTA), the ratio of PTA to ethylene glycol was fixed at 1:1.4, and the catalyst Sb was added. 2 O 3 (150ppm / gPTA), followed by ultrasonic stirring for 5min to prepare a polyester slurry.

[0064] Step (3) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution were prepared using DMF as a solvent, wherein the spinning concentration of PAN was 4 wt % and the spinning concentration of APP was 15 wt %. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) were added into a glass bottle, stirred on a magnetic heating stirrer for 5 h to uniformly mix the solution, and then allowed to stand for 10 h to eliminate bubbles, thereby preparing an electrospinning solution.

[0065] Step (4) Preparation of tourmaline fiber The electrospinning solution prepared in step (3) is added, and the tourmaline crystals are crushed into 5 mm blocks by a rotary crusher, and then crushed into 15 micron coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5 micron; silver compounds such as silver lactate, silver nitrate, and silver sulfate are selected to prepare a 0.05M aqueous solution as a silver-carrying treatment solution for tourmaline; the 0.5 micron particle size water slurry is mixed with the tourmaline silver-carrying treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5:90; the pH is adjusted to 9 .5, stir for 1 hour in a dark place to allow it to fully react and complete the silver-loading treatment of tourmaline, then mix it with the viscose fiber liquid, control the weight ratio of silver-loading tourmaline to viscose fiber to be 2:99; and control the viscosity for 25 seconds, the solid content in the silver-loading tourmaline slurry is not less than 10% by weight; after 2 conventional filtrations and the last 2 layers of silk cloth filtration, control the fineness to be between 0.01 microns; carry out wet spinning, control the speed to 40 m / min, and coagulate in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the tourmaline fiber is prepared.

[0066] Step (5) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU was fixed at 1:1. First, 35 g DMAc was weighed into a reagent bottle and placed on a stirring table for stirring. Then, 3.3 g PPSU particles and 1.5 g PU particles were weighed in sequence and slowly poured into the reagent bottle. Then, the electrospinning solution prepared in step (3) was added while stirring and 1.5 g BIP was slowly added with a syringe. The mouth of the reagent bottle was sealed with a sealing strip and stirred for 5 h to obtain the final PPSU / PU electrospinning solution. The spinning solution was absorbed with a 2 mL syringe and fixed on the perfusion system of the spinning machine. The front needle of the syringe was connected to a high-voltage power supply. A layer of polypropylene non-woven fabric was tightly attached to the grounded metal roller as a receiving substrate. Then, the receiving roller, the perfusion system, the slide and the high-voltage power supply were turned on in sequence for spinning to prepare an electrospun PPSU / PU fiber sponge.

[0067] Step (6) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 0.6 mm, the receiving distance is 15 cm, the spinning speed is 0.2 mL / h, the spinning voltage is constant at 12 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (5) is placed, and the tourmaline fiber prepared in step (4) is sprayed with two larger polytetrafluoroethylene (PTFE) woven meshes in a cotton drying room and thermally bonded at 100°C for 2 minutes; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

[0068] Comparison of detection experiments: The multilayer composite flame-retardant fiber materials obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing methods are as follows: Far infrared performance test Directly measure the ability of a sample to emit far-infrared light after receiving external energy. This usually requires the use of a far-infrared radiation measurement system that can cover the far-infrared band (such as 5μm~14μm) and measure the radiation intensity of the sample. The specific operation includes placing the standard blackbody plate and the sample on a hot plate in turn, adjusting the surface temperature of the hot plate, and then measuring the radiation intensity of the standard blackbody plate and the sample respectively.

[0069] Flame retardant performance test The sample is placed vertically on the combustion device, the lower end of the sample is ignited, the combustion of the sample is observed, the burning time and burning length are recorded, and its combustion performance is evaluated by referring to the cone calorimeter method, vertical combustion test and horizontal combustion test, etc. These test methods evaluate the flame retardant properties of the material by placing the sample on a specific combustion device, igniting one end or the lower end, observing the spread of the flame and the combustion characteristics of the sample, and measuring parameters such as burning time, burning length, and burning rate.

[0070] Antibacterial performance test Antibacterial performance testing is an important means to evaluate the ability of materials or products to resist or inhibit bacterial growth. These test methods are usually divided into qualitative tests and quantitative tests, which aim to determine whether the product has antibacterial effects and evaluate its specific antibacterial degree. The bacterial solution is dripped onto the sample, and a film is laid to evenly coat the sample surface. After 30 minutes of contact, it is observed whether an inhibition zone is formed around the sample to determine its antibacterial performance. The sample is embedded in a bacterial culture medium inoculated with a certain amount of bacterial solution. After 1-5 hours of incubation, the bacterial growth is observed and the antibacterial performance of the sample is determined by comparing it with the reference sample.

[0071] Table 1 Far infrared performance test

[0072] As can be seen from Table 1, Example 2 is the best and Comparative Example 1 is the worst. The tourmaline powder in the examples has far-infrared radiation performance, and its far-infrared radiation performance can be further improved by modification. The distribution and performance of the modified tourmaline powder in the composite material will directly affect the far-infrared radiation temperature rise value. The far-infrared radiation temperature rise value in Example 2 is high and the performance is good.

[0073] Table 2 Flame retardant performance test

[0074] As can be seen from Table 2, Example 2 is the best and Comparative Example 1 is relatively poor. The oxygen index in Example 2 is the highest, and this type of material has good flame retardant properties, while the oxygen index in Comparative Example 2 is the lowest and is easy to burn; DOPO in the example is a highly efficient flame retardant, and its combination with GO can significantly improve the flame retardant properties of the composite material. The addition of flame retardant DOPO-GO is beneficial to improving the flame retardant effect. The spinning concentration of PAN solution and PAN / APP mixed solution, the addition amount of modified tourmaline powder and polyester slurry and their dispersibility will affect the flame retardant properties of the spun fiber.

[0075] Table 3 Antibacterial performance test

[0076] As can be seen from Table 3, Example 2 is the best, while Comparative Example 1 is relatively poor. The antibacterial rate of Example 2 is the highest, while the antibacterial rate of the comparative example is relatively low. In the example, far-infrared radiation can promote blood circulation and microcirculation, improve body immunity, and thus indirectly enhance the antibacterial effect of the material; the nanostructure of GO is conducive to enhancing the antibacterial performance, especially if other antibacterial components are loaded on the surface of GO, silver ions have antibacterial properties and can effectively inhibit the growth of a variety of bacteria. The silver loading of tourmaline will affect the loading amount and stability of silver ions, which is conducive to improving the antibacterial performance of the material.

[0077] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A preparation method for a multi-layer composite flame-retardant fiber material combining far infrared and negative ions, characterized in that: include: Tourmaline powder modification, preparation of flame retardant from modified GO, preparation of polyester slurry, preparation of electrospinning solution, preparation of tourmaline fiber, flame retardant composite fiber, preparation of electrospun PPSU / PU fiber sponge, preparation of multi-layer composite flame retardant fiber material.

2. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 1, characterized in that: Step (1) Tourmaline powder modification Add tourmaline powder into a three-necked flask, and then add coupling agent titanate, polyvinyl alcohol and silane respectively; add reaction solvent (toluene) into the flask and continue the reaction in an oil bath; use a centrifuge to separate toluene from the reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder; Step (2) Modification of GO to prepare flame retardant DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to DMF, and stirred to fully dissolve DOPO for use; graphene oxide is placed in a DMF solution for ultrasonic dispersion, so that the GO (graphene oxide) sheets are separated and evenly dispersed in DMF (N,N-dimethylformamide); then the dispersed GO is added to the above-dissolved DOPO, and stirred to react under a nitrogen atmosphere; the liquid after the reaction is filtered under reduced pressure to obtain a black powder, which is then repeatedly washed with DMF to remove DOPO that does not participate in the reaction, and finally placed in a vacuum oven for drying to obtain a modified flame retardant DOPO-GO; Step (3) Preparation of polyester slurry Mixing ethylene glycol-based carbon black slurry and terephthalic acid (PTA), adding the modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb2O3 (antimony trioxide), and then ultrasonically stirring to prepare a polyester slurry; Step (4) Preparation of electrospinning solution Using DMF as solvent, respectively prepare a PAN (polyacrylonitrile) solution and a PAN / APP mixed solution, add the solvent and the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) into a glass bottle, stir the solution on a magnetic heating stirrer to make the solution uniformly mixed, and then let it stand to eliminate bubbles, thereby preparing an electrospinning solution; Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into blocks by a rotary crusher, and then crushed into micron coarse powder by a Raymond mill, and finally wet-ground into a micron water slurry by a sand mill; silver compounds such as silver lactate, silver nitrate, and silver sulfate are selected to prepare an aqueous solution as a silver-carrying treatment solution for tourmaline; the water slurry with micron particles is mixed with the tourmaline silver-carrying treatment solution, the pH is adjusted to a certain value, and stirred in a dark environment to allow sufficient reaction to complete the silver-carrying treatment of the tourmaline, and then mixed with the viscose fiber solution to control the weight ratio of the silver-carrying tourmaline to the viscose fiber to a certain value; and the viscosity is controlled; after conventional filtration and final filtration with silk cloth, the fineness is controlled for wet spinning, and the speed is controlled for coagulation in an acid bath; after post-treatment such as plasticizing, drawing, cutting, drying, and packaging, the tourmaline fiber is prepared; Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO (dimethyl sulfoxide) solution and ultrasonically dispersed for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of MCC (microcrystalline cellulose) composite fibers under traction; the primary filaments are drawn out in a single strand in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a certain temperature and humidity to dry naturally, thereby obtaining a flame-retardant composite fiber; Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU (polyphenylene sulfone resin) to PU (polyurethane) is fixed; first, DMAc (N, N-dimethylacetamide) is added to a reagent bottle, and the bottle is placed on a stirring table for stirring, and then PPSU particles and PU particles are added in sequence and slowly poured into the reagent bottle, and BIP (blocked isocyanate) is slowly added to the PPSU / PU spinning solution with a syringe while stirring, and the mouth of the reagent bottle is sealed with a sealing strip for stirring to obtain the final PPSU / PU electrospinning solution; the spinning solution is sucked with a syringe and fixed on the perfusion system of the spinning machine and the front needle of the syringe is connected to a high-voltage power supply, and a layer of polypropylene non-woven fabric is tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, the perfusion system, the slide and the high-voltage power supply are turned on in sequence for spinning to prepare an electrospun PPSU / PU fiber sponge; Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is a certain value, the receiving distance, spinning speed, and spinning voltage are determined, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7), the tourmaline fiber prepared in step (5), and the flame-retardant composite fiber prepared in step (6) are placed in two larger polytetrafluoroethylene (PTFE) woven nets and sprayed in a cotton drying room. Under thermal bonding, the area and mass of the PTFE woven net are selected to pressurize the multi-layer composite fiber web. The PTFE woven net can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

3. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 2, characterized in that: Step (1) Tourmaline powder modification Add tourmaline powder into three three-necked flasks, and then add coupling agents titanate, polyvinyl alcohol and silane respectively; make the mass fraction of the coupling agent in the whole mixture system be 1-3%; add reaction solvent (toluene) into the flask and continue to react in an oil bath at 90-96°C for 1-4 hours; use a centrifuge to separate toluene and reaction products of the three reaction solutions, dry and grind the products to obtain modified tourmaline powder.

4. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 2, characterized in that: Step (2) Modification of GO to prepare flame retardant 1-6g DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to 45-50mL DMF, and stirred at 60-65°C for 10-15min to fully dissolve DOPO for use; 1-5g graphene oxide is placed in a DMF solution and ultrasonically dispersed for 20-25min to separate the GO sheets and evenly disperse them in DMF; then the dispersed GO is added to the above-dissolved DOPO, and stirred to react for 1-7.5h under a nitrogen atmosphere (a thermometer is used to ensure that the reaction temperature in a nitrogen atmosphere is 55-60°C); the liquid after the reaction is filtered under reduced pressure to obtain a black powder, which is then repeatedly washed with DMF for 1-4 times to remove DOPO that does not participate in the reaction, and finally placed in a vacuum oven at -50--60°C for 10-15h to obtain a modified flame retardant DOPO-GO.

5. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 4, characterized in that: Step (3) Preparation of polyester slurry 1-5wt% ethylene glycol-based carbon black slurry and terephthalic acid (PTA) are mixed, and the ratio of PTA to ethylene glycol is fixed at 1-5:1.4-2.

5. The modified flame retardant DOPO-GO prepared in step (2) and the catalyst Sb2O3 (300-350ppm / gPTA) are added, followed by ultrasonic stirring for 15-20min to prepare a polyester slurry.

6. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 5, characterized in that: Step (4) Preparation of electrospinning solution A PAN solution and a PAN / APP mixed solution are prepared respectively using DMF as a solvent, wherein the spinning concentration of PAN is 5-12wt% and the spinning concentration of APP is 18-30wt%. The solvent, the modified tourmaline powder prepared in step (1), and the polyester slurry prepared in step (3) are added into a glass bottle, stirred on a magnetic heating stirrer for 10-12h to uniformly mix the solution, and then allowed to stand for 12-20h to eliminate bubbles, thereby preparing an electrospinning solution.

7. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 6, characterized in that: Step (5) Preparation of tourmaline fiber The electrospinning solution prepared in step (4) is added, and the tourmaline crystals are crushed into 8-25 mm blocks by a rotary crusher, and then crushed into 20-40 micron coarse powder by a Raymond mill, and finally wet-ground by a sand mill to a water slurry with an average particle size of 0.5-2.5 microns; silver compounds such as silver lactate, silver nitrate, and silver sulfate are selected to prepare a 0.05-1M aqueous solution as a silver-carrying treatment solution for tourmaline; the water slurry with a particle size of 0.5-2.5 microns is mixed with the tourmaline silver-carrying treatment solution, and the weight ratio of silver to tourmaline is controlled to be 0.5-10:90-99.5; the pH is adjusted to 9.5- 10.5, stirring for 1-3 hours in a dark environment to allow it to fully react and complete the silver-loading treatment of tourmaline, and then mixing with the viscose fiber liquid, controlling the weight ratio of silver-loading tourmaline to viscose fiber to be 1-20:99-80; and controlling the viscosity for 30-60 seconds, and the solid content in the silver-loading tourmaline slurry is not less than 15-20% by weight; after 1-3 conventional filtrations and the last 1-3 layers of silk cloth filtration, the fineness is controlled to be between 0.01-1 micron; wet spinning is carried out at a speed of 40-100 m / min, and coagulation is carried out in an acid bath; after post-treatments such as plasticizing, drawing, cutting, drying, and packaging, the preparation of tourmaline fiber is obtained.

8. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 6, characterized in that: Step (6) Flame retardant composite fiber First, the DOPO-GO prepared in step (2) is added to a DMSO solution and ultrasonically dispersed for at least 10-15 minutes for later use; the electrospinning solution prepared in step (4) is transferred to a disposable needle tube, and water is used as a coagulation bath. A wet spinning machine is used to spin the primary filaments of the MCC composite fiber under traction; the primary filaments are drawn out in the coagulation bath, clamped on a single fiber clip, and placed in a constant temperature and humidity environment with a temperature of 15-20° C. and a humidity of 55-60% to dry naturally to obtain a flame-retardant composite fiber.

9. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 8, characterized in that: Step (7) Preparation of electrospun PPSU / PU flame retardant fiber sponge The mass ratio of PPSU to PU is fixed at 1-4:1-3; first, 40-48g DMAc is weighed into a reagent bottle and placed on a stirring table for stirring, then 5.5-9.6g PPSU particles and 2.4-5.5g PU particles are weighed in turn and slowly poured into the reagent bottle, then PPSU / PU spinning solution is added and 1.8-2.8g BIP is slowly added with a syringe while stirring, and the mouth of the reagent bottle is sealed with a sealing strip and stirred for 12-15h to obtain the final PPSU / PU electrospinning solution; 2-5 5-10mL syringes are used to absorb the spinning solution and fixed on the perfusion system of the spinning machine and the front needle of the syringe is connected to the high-voltage power supply, a layer of polypropylene non-woven fabric is tightly attached to the grounded metal roller as a receiving substrate, and then the receiving roller, the perfusion system, the slide and the high-voltage power supply are turned on in turn for spinning to prepare the electrospun PPSU / PU fiber sponge.

10. The preparation of a multi-layer composite flame-retardant fiber material combining far infrared and negative ions according to claim 9, characterized in that: Step (8) Preparation of multi-layer composite flame retardant fiber material Electrospinning process parameters: the inner diameter of the syringe needle is 0.6-2.6 mm, the receiving distance is 20-25 cm, the spinning speed is 0.5-0.8 mL / h, the spinning voltage is constant at 15-20 kV, the micron fiber web is placed on the drum of the electrospinning device, the spinning solution is injected into the syringe for spinning to prepare a single-layer composite fiber web, the electrospun PPSU / PU flame-retardant fiber sponge prepared in step (7) is placed, the tourmaline fiber prepared in step (5) and the flame-retardant composite fiber prepared in step (6) are sprayed in two larger polytetrafluoroethylene (PTFE) woven meshes in a cotton drying room, and thermally bonded at 135-150° C. for 1-7 minutes; the area and mass of the PTFE woven mesh are selected to exert a pressurizing effect on the multi-layer composite fiber web, and the PTFE woven mesh can be directly peeled off after being taken out of the drying room; and a multi-layer composite flame-retardant fiber material is prepared.

Citation Information

Patent Citations

  • Preparation method of negative ion release, far-infrared and fire retardation composite function polyester fibers

    CN104988594A

  • Preparation method for composite flame retardant

    CN106750525A

  • Flame-retardant polyacrylonitrile composite fiber with skin-core structure as well as preparation method and application of flame-retardant polyacrylonitrile composite fiber

    CN114164521A

  • Flame-retardant fluffy warm-keeping nanofiber cotton-blended spunlace filler and production process thereof

    CN118326617A

  • Multi-layer flame-retardant composite fabric based on pre-oxidized fiber and preparation method of multi-layer flame-retardant composite fabric

    CN118478570A